A Study on the Adverse Drug Reactions Induced by Anti Epileptic Drugs in the Epileptic Patients - Keerthy Jayalekshmi, Kavitha Palanisamy, Sambathkumar Ramanathan, Sruthi Akela (Journal of Applied Pharmaceutical Science, 2016)
Epilepsy is a chronic disorder of the brain that affects people worldwide. The aim of this work was to study the adverse drug reactions (ADRs) induced by the antiepileptic drugs (AEDs) in epileptic patients. This prospective study was carried out for six months, from April 2014 to September 2014, in a tertiary teaching care hospital, Erode. The study included epileptic patients, both male and female of all age groups, undergoing treatment with AEDs. A total of 180 epileptic patients were monitored, 60% were male and 40% were females. Majority of the study population were adults. Majority of the epileptic patients were affected with generalized seizure (46.66%). Monotherapy was preferred more (71.1%) over combination therapy (34.44%). Sodium valproate (24.4%) was the most prescribed drug in monotherapy followed closely by Phenytoin (18.3%). Most prescribed two drug combination was of Sodium valproate and Carbamazepine (8.3%) followed by Phenytoin and Phenobarbitone (6.67%). Most common ADR was memory loss, hepatotoxicity, aggression and reduced learning. Sodium valproate was found to induce more number of ADRs followed by Carbamazepine and Phenytoin. Treatment with antiepileptic drugs was continued in all cases, except in three cases of skin rashes.
Keywords: Epilepsy, anti epileptic drug, adverse drug reactions.